Alternative Mitophagy Protects the Heart Against Obesity-Associated Cardiomyopathy. Issue 12 (3rd December 2021) - Tong, Mingming; Saito, Toshiro; Zhai, Peiyong; Oka, Shin-ichi; Mizushima, Wataru; Nakamura, Michinari; Ikeda, Shohei; Shirakabe, Akihiro; Sadoshima, Junichi
Abstract : Rationale: Obesity-associated cardiomyopathy characterized by hypertrophy and mitochondrial dysfunction. Mitochondrial quality control mechanisms, including mitophagy, are essential for the maintenance of cardiac function in obesity-associated cardiomyopathy. However, autophagic flux peaks at around 6 weeks of high-fat diet (HFD) consumption and declines thereafter. Objective: We investigated whether mitophagy is activated during the chronic phase of cardiomyopathy associated with obesity (obesity cardiomyopathy) after general autophagy is downregulated and, if so, what the underlying mechanism and the functional significance are. Methods and Results: Mice were fed either a normal diet or a HFD (60 kcal% fat). Mitophagy, evaluated using Mito-Keima, was increased after 3 weeks of HFD consumption and continued to increase after conventional mechanisms of autophagy were inactivated, at least until 24 weeks. HFD consumption time-dependently upregulated both Ser555-phosphorylated Ulk1 (unc-51 like kinase 1) and Rab9 (Ras-related protein Rab-9) in the mitochondrial fraction. Mitochondria were sequestrated by Rab9-positive ring-like structures in cardiomyocytes isolated from mice after 20 weeks of HFD consumption, consistent with the activation of alternative mitophagy. Increases in mitophagy induced by HFD consumption for 20 weeks were abolished in cardiac-specific ulk1 knockout mouse hearts, in which both diastolic and systolic dysfunction were exacerbated. Rab9 S179A knock-in mice, in which alternative mitophagy is selectively suppressed, exhibited impaired mitophagy and more severe cardiac dysfunction than control mice following HFD consumption for 20 weeks. Overexpression of Rab9 in the heart increased mitophagy and protected against cardiac dysfunction during HFD consumption. HFD-induced activation of Rab9-dependent mitophagy was accompanied by upregulation of TFE3 (transcription factor binding to IGHM enhancer 3), which plays an essential role in transcriptional activation of mitophagy. Conclusions: Ulk1-Rab9-dependent alternative mitophagy is activated during the chronic phase of HFD consumption and serves as an essential mitochondrial quality control mechanism, thereby protecting the heart against obesity cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.